Young change makers : the rise of Hong Kong airlines - Tong, Zelin (Enrich Professional Publishing, 2017)
Hong Kong Airlines has grown gradually from being a regional airline to a global airline after a decade of development. The key to its speedy growth in the highly competitive aviation sector is its power in service innovation as well as its unique and energetic service culture. This book tries to extract, via lessons from this young airline, the power of sincerity, power of passion, power of innovation, power of learning, power of action, power of flexibility, power of a team, power of communication, power of happiness, power of endeavor, and power of commitment, on which an iceberg model of Ho.